Factors that Influence Women's Political Participation in the Mayoral Election in Bhayangkara Subdistrict, Jayapura City - Fatimah, Siti; M. Seseray, Maris; Andry, Andry; Susilawaty, Susilawaty; Ambawang, Laela T; Sumantri, Sumantri (Jurnal Pemerintahan dan Politik Lokal, 2025)
The main focus of this research is to identify factors that influence women's political participation in the region. The method used is qualitative, with analysis and problem formulation based on field data. The research informants were the heads of the neighborhood units (RW) in Bhayangkara Village. Data were obtained through three methods: first, data collection from interviews and observations recorded in field notes, including official documents and photographs; second, data reduction by summarizing and selecting important information; and third, drawing conclusions. The results of the research indicate that women's political participation is influenced by several factors, including: (1) An increasingly less dominant patriarchal culture; (2) Lack of systematic political education despite good understanding; (3) Minimal structural barriers, but there are internal factors such as low interest; (4) Double burdens managed with family support; (5) Low violence and intimidation, although there are cases of verbal violence; (6) Affirmative policies hampered by socialization and funding; (7) Growing gender education and awareness despite lingering stigma; (8) Limited support from non-governmental organizations; (9) Positive but uneven social change; and (10) Unstructured mentorship networks. Based on these findings, the study recommends socialization on gender equality, strengthening political education, increasing women's capacity, and developing mentorship programs and institutional support to strengthen women's political participation at the local level.